DEVELOPING OF STORY WRITING TEACHING MATERIALS FOR ELEMENTARY SCHOOL IN THE INDEPENDENT ERA LEARNING SOCIETY 5.0 BASED ON LOCAL WISDOM - Endang Setyowati; Lis Susilawati (Journey: Journal of English Language and Pedagogy, 2022)
Given the swift currents of globalization and making it easier for foreign cultures to enter and influence the younger generation in Indonesia, especially children. In addition, teaching materials are also needed whose approach is in accordance with the times. Therefore, the researchers developed an elementary school teaching material that was in accordance with the independent era of learning society 5.0 based on local wisdom. The general objective of this research is to produce a product in the form of teaching materials for writing children's stories in the independent era of learning society 5.0 based on local wisdom. The specific objectives of this research are (1) to produce learning materials for writing children's stories in the independent era of learning society 5.0 based on local wisdom, and (2) describing the feasibility of teaching materials to write children's stories in the independent era of learning society 5.0 based on local wisdom that has been developed.The research model used is the Borg and Gall research model. The research model used by Borg and Gall is the Research and Development (R & D) approach. The results obtained from the validation carried out by content (material) experts, namely 87% with the validity level being quite valid with small revisions, and validation by learning media experts, namely 85% with the validity level being quite valid and requiring minor revisions. The results of the development of teaching materials for writing children's stories in the independent era of learning society 5.0 based on local wisdom for elementary school students, especially grades IV until VI in Malang is at 83%, which means that the teaching materials for writing children's stories are suitable for use.